The contribution of nitrogen deposition to the photosynthetic capacity of forests. Issue 1 (28th February 2013) - Fleischer, K.; Rebel, K. T.; van der, M. K.; Erisman, J. W.; Wassen, M. J.; van, E. E.; Montagnani, L.; Gough, C. M.; Herbst, M.; Janssens, I. A.; Gianelle, D.; Dolman, A. J.
Abstract [1] Global terrestrial carbon (C) sequestration has increased over the last few decades. The drivers of carbon sequestration, the geographical spread and magnitude of this sink are however hotly debated. Photosynthesis determines the total C uptake of terrestrial ecosystems and is a major flux of the global C balance. We contribute to the discussion on enhanced C sequestration by analyzing the influence of nitrogen (N) deposition on photosynthetic capacity (Amax) of forest canopies. Eddy covariance measurements of net exchange of carbon provide estimates of gross primary production, from which Amax is derived with a novel approach. Canopy Amax is combined with modeled N deposition, environmental variables and stand characteristics to study the relative effects on Amax for a unique global data set of 80 forest FLUXNET sites. Canopy Amax relates positively to N deposition for evergreen needleleaf forests below an observed critical load of ~ 8 kg N ha–1 yr–1, with a slope of 2.0 ± 0.4 (S.E.) µmol CO2 m–2 s–1 per 1 kg N ha–1 yr–1. Above this threshold canopy Amax levels off, exhibiting a saturating response in line with the N saturation hypothesis. Climate effects on canopy Amax cannot be separated from the effect of N deposition due to considerable covariation. For deciduous broadleaf forests and forests in the temperate (‐continental) climate zones, the analysis shows the N deposition effect to be either small or absent. Leaf area index and foliar N concentration are positively but weakly related to Amax. We conclude that flux tower measurements of C fluxes provide valuable data to study physiological processes at the canopy scale. Future efforts need to be directed toward standardizing measures N cycling and pools within C monitoring networks to gain a better understanding of C and N interactions, and to disentangle the role of climate and N deposition in forest ecosystems.